2016
DOI: 10.1017/s0047279416000593
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Welfare State in Pension Markets: Mitigating High Charges for Low-Income Savers in the United Kingdom and Israel

Abstract: How does the rising 'regulatory welfare state' address social policy concerns in pension markets? This study examines this question by comparing the regulatory responses to high charges paid by low-income workers in pension markets in the UK and Israel. In the UK, with the recognition that the market would not cater to low-income workers, the regulatory response was the creation of a publicly operated low-cost pension fund (NEST), a 'public option' within the market. This allowed low-income workers access to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…The reasons for these reforms include ideological preferences for smaller government, fiscal pressures to lower the costs of the welfare state, decades-long criticism of welfare bureaucracies as inefficient and paternalistic and attempts to promote social innovation and entrepreneurship. But regardless of motivation, these reforms have been a fertile ground for the proliferation of market and, at times, network forms of welfare governance and the rise of the regulatory state inside the welfare state (Gilbert, 2013;Levi-Faur, 2014;Benish et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for these reforms include ideological preferences for smaller government, fiscal pressures to lower the costs of the welfare state, decades-long criticism of welfare bureaucracies as inefficient and paternalistic and attempts to promote social innovation and entrepreneurship. But regardless of motivation, these reforms have been a fertile ground for the proliferation of market and, at times, network forms of welfare governance and the rise of the regulatory state inside the welfare state (Gilbert, 2013;Levi-Faur, 2014;Benish et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, we have witnessed a major transformation in modern welfare states, with a movement towards the privatisation, decentralisation and commercialisation of social welfare. A new role for government is taking shape, often referred to as the ‘enabling state’ (Gilbert, ), or the ‘regulatory welfare state’ (Benish, Haber, & Eliahou, ; Haber, ; Leisering, ; Levi‐Faur, ). Within this role, instead of directly financing and delivering social welfare goods and services, welfare states increasingly rely on private actors and market‐type arrangements, reshaping the relationships between authorities, private providers and citizens (Ascoli & Ranci, ; Kotkas, ).…”
mentioning
confidence: 99%
“…The findings suggest the occurrence and significance of social policy aimed at ensuring citizens' access to services provided in the market. This study adds to a growing number of studies which show the prevalence and the variety in the use of this kind of policy in different policy sectors and national settings, including electricity, housing credit, water and pension fees, in the UK, Sweden, Israel and the EU (see for example Haber, 2016;Benish et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In this research, we place policy aimed at preventing the termination of services due to financial hardship within the context of this literature of welfare through regulation (or 'regulatory welfare'), and focus on the housing credit sector, and specifically on the prevention of housing credit related eviction and repossession. Recent research on this issue has found cross national differences in how access to such services as electricity, water, rail, post and pension fees is regulated in the market (Haber, 2011;Pflieger, 2014;Eckert, 2015;Haber, 2016;Benish, Haber, & Eliahou, 2016).…”
Section: Theoretical Background: Welfare Through-regulatory-means Andmentioning
confidence: 99%